Nurturing emotional foundations: Investigating the impact of parenting style and parenting stress on early childhood emotional well-bein - Aprianti, Wahyuni Putri; Yandri, Hengki; Vitaloka, Wulansari (Universitas Islam Negeri Raden Intan Lampung, 2024)
Background : Parenting styles and parental stress significantly impact the emotional development of young children. Authoritative parenting promotes better emotional regulation, while authoritarian and permissive styles may hinder it. This study examines these effects in Kerinci Regency, Indonesia.Aim : To investigate the relationship between parenting styles, parental stress, and the emotional state of children aged 0-6 years in Kerinci Regency.Method : A quantitative survey and correlational design were used, involving 57 parents of young children. Validated questionnaires assessed parenting styles, parental stress, and children's emotional regulation. Simple and multiple regression analyses were conducted.Result : Significant associations were found between parenting styles, parental stress, and children's emotional states. Authoritative parenting was linked to better emotional regulation, while authoritarian and permissive styles were linked to poorer emotional states. Higher parental stress correlated with worse emotional outcomes in children.Conclusion : Parenting style and stress significantly impact children's emotional health. Supportive parenting and effective stress management promote better emotional regulation. Interventions to support positive parenting and stress management are recommended for improving children's emotional well-being.